Cannabis Use, Schizotypy and Kamin Blocking Performance - Dawes, Christopher; Bickerdike, Andrea; O'Neill, Cian; Carneiro Pereira, Sarah; Waddington, John L.; Moran, Paula M.; O'Tuathaigh, Colm M. P. (Frontiers in Psychiatry, 2021)
Cannabis use has been associated with increased risk for a first episode of psychosis and inappropriate assignment of salience to extraneous stimuli has been proposed as a mechanism underlying this association. Psychosis-prone (especially schizotypal) personality traits are associated with deficits in associative learning tasks that measure salience allocation. The aim of this study was to examine the relationship between history of cannabis use and Kamin blocking (KB), a form of selective associative learning, in a non-clinical sample. Additionally, KB was examined in relation to self-reported schizotypy and aberrant salience scale profiles. A cross-sectional study was conducted in 307 healthy participants with no previous psychiatric or neurological history. Participants were recruited and tested using the Testable Minds behavioural testing platform. KB was calculated using Oades' “mouse in the house task”, performance of which is disrupted in schizophrenia patients. Schizotypy was measured using the Schizotypal Personality Questionnaire (SPQ), and the Aberrant Salience Inventory (ASI) was used to assess self-reported unusual or inappropriate salience. The modified Cannabis Experience Questionnaire (CEQm) was used to collect detailed history of use of cannabis and other recreational drugs. Regression models and Bayesian t-tests or ANOVA (or non-parametric equivalents) examined differences in KB based on lifetime or current cannabis use (frequent use during previous year), as well as frequency of use among those who had previously used cannabis. Neither lifetime nor current cannabis use was associated with any significant change in total or trial-specific KB scores. Current cannabis use was associated with higher Disorganised SPQ dimension scores and higher total and sub-scale values for the ASI. A modest positive association was observed between total KB score and Disorganised SPQ dimension scores, but no relationships were found between KB and other SPQ measures. Higher scores on “Senses Sharpening” ASI sub-scale predicted decreased KB score only in participants who have not engaged in recent cannabis use. These results are discussed in the context of our understanding of the effects of long-term cannabis exposure on salience attribution, as well as inconsistencies in the literature with respect to both the relationship between KB and schizotypy and the measurement of KB associative learning phenomena.